2018
DOI: 10.3168/jds.2017-13654
|View full text |Cite
|
Sign up to set email alerts
|

Screening probiotics from Lactobacillus strains according to their abilities to inhibit pathogen adhesion and induction of pro-inflammatory cytokine IL-8

Abstract: Probiotics can be screened according to their abilities to inhibit pathogen adhesion and inhibit the production of pro-inflammatory cytokines. Eleven Lactobacillus strains isolated from traditional fermented dairy foods in Xinjiang, China, were studied for their potential to inhibit adhesion of Escherichia coli to intestinal epithelial cells and to inhibit E. coli-induced production of interleukin (IL)-8 by intestinal epithelial cells. The results showed that the 11 strains could inhibit adhesion of E. coli to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…1). This property is strain specific and it is usually screened in vitro using cell lines infected with pathogens (Walsham et al 2016; Jessie Lau and Chye 2018; Tuo et al 2018). For instance, several clinical trials have demonstrated the effectiveness of Lactobacillus rhamnosus LGG against vancomycin-resistant enterococci in colonized patients (Szachta et al 2011; Manley et al 2007).…”
Section: Antagonism Against Pathogensmentioning
confidence: 99%
“…1). This property is strain specific and it is usually screened in vitro using cell lines infected with pathogens (Walsham et al 2016; Jessie Lau and Chye 2018; Tuo et al 2018). For instance, several clinical trials have demonstrated the effectiveness of Lactobacillus rhamnosus LGG against vancomycin-resistant enterococci in colonized patients (Szachta et al 2011; Manley et al 2007).…”
Section: Antagonism Against Pathogensmentioning
confidence: 99%
“…These beneficial benefits may include preventing diarrhea ( Staudacher, 2015 ; Sinclair et al, 2016 ; Kim et al, 2018 ), modulating the intestinal community ( Marteau et al, 2002 ; Xie et al, 2016 ), improving lactose tolerance ( Mustapha et al, 1997 ; Staudacher, 2015 ; Oak and Jha, 2018 ), reducing the serum cholesterol level ( Choi et al, 2015 ; Kobyliak et al, 2016 ), suppressing pathogens ( Kim et al, 2014 ; Tuo et al, 2018 ), and boosting the immune system ( Dimitrijevic et al, 2014 ; Kemgang et al, 2014 ). To maximize these functions, Lactobacillus strains must be able to adhere to and colonize the gastro-intestinal tract ( Ljungh and Wadstrom, 2006 ; Tuo et al, 2018 ). Therefore, one important criterion in selecting probiotic bacteria is their ability to adhere to epithelial cells of the intestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…L. casei significantly inhibits the growth of pathogenic bacteria as well. A recent study showed that 11 Lactobacillus strains can inhibit adhesion of E. coli to Caco‐2 cells, with L. plantarum and LGG exhibiting higher inhibition rates (Tuo et al, 2018). Studies have shown that L. acidophilus LA1 inhibits the adhesion of pathogenic E. coli , Salmonella typhimurium and Yersinia pseudotuberculosis to cells (Bernet et al, 1994).…”
Section: Discussionmentioning
confidence: 99%